2021
DOI: 10.1002/mrm.28946
|View full text |Cite
|
Sign up to set email alerts
|

Improving homogeneity in abdominal imaging at 3 T with light, flexible, and compact metasurface

Abstract: Purpose: Radiofrequency field inhomogeneity is a significant issue in imaging large fields of view in high-and ultrahigh-field MRI. Passive shimming with coupled coils or dielectric pads is the most common approach at 3 T. We introduce and test light and compact metasurface, providing the same homogeneity improvement in clinical abdominal imaging at 3 T as a conventional dielectric pad. Methods: The metasurface comprising a periodic structure of copper strips and parallel-plate capacitive elements printed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…The B 1 + CV describes the spread of the transmit magnetic-field inhomogeneity within the masked region. Coil transmit efficiency (TrE) is defined as B 1 + inv.targ / √ P. Here, P denotes the transmitted power equal to V ref 2 /R with coil impedance R = 50 Ω, and B 1 + inv.targ is a constant coefficient corresponding to the amplitude of a rectangular inversion RF pulse with the length of 𝜏 = 1 ms: B 1 + inv.targ = π/(2πγ⋅τ) where γ = 42.57⋅10 6 Hz/T -gyromagnetic ratio. These values characterizing the Nova and MW1 coils obtained for the 2 volunteers are provided in Table 4.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…The B 1 + CV describes the spread of the transmit magnetic-field inhomogeneity within the masked region. Coil transmit efficiency (TrE) is defined as B 1 + inv.targ / √ P. Here, P denotes the transmitted power equal to V ref 2 /R with coil impedance R = 50 Ω, and B 1 + inv.targ is a constant coefficient corresponding to the amplitude of a rectangular inversion RF pulse with the length of 𝜏 = 1 ms: B 1 + inv.targ = π/(2πγ⋅τ) where γ = 42.57⋅10 6 Hz/T -gyromagnetic ratio. These values characterizing the Nova and MW1 coils obtained for the 2 volunteers are provided in Table 4.…”
Section: 3mentioning
confidence: 99%
“…The B 1 + inhomogeneity leads to changes in the signal intensity and contrast, complicating image evaluation and diagnosis. To face this problem, some works have considered antennas incorporating new materials such as ceramics or metamaterials that modify the field distribution in the subject 5–7 . Another state‐of‐art solution is parallel transmission (pTx), 8–10 providing control over the B 1 + of several individual transmit elements to achieve more uniform excitation under given power and SAR constraints.…”
Section: Introductionmentioning
confidence: 99%
“…This artificial dielectric mimicked the action of an equivalently-sized dielectric pad with ε r = 120, but was not ideal in terms of the orientation of the secondary B-field created, and the fact that several PCB layers were needed which gave rise to a very rigid structure. They recently showed an improved design approach for abdominal imaging at 3 T [ 82 ] using an artificial dielectric produced on a thin single double-sided low-loss PCB with capacitors formed by the overlap of conductive patches on either side of the flexible PCB connected by thin copper strips. Results, shown in Fig.…”
Section: Design Of Metamaterials/metasurfaces and Artificial Dielectr...mentioning
confidence: 99%
“…The use of high permittivity layer (HPL) under neath of an array of resonators is the main difference between the current device and our previous design 35 . Many research groups have shown that the use of DPs (high permittivity materials) can increase the homogeneity of the transmit field in MRI 12,28,38,39 . In our design, we used the HPL to further improve the transmit efficiency due to the induced displacement current and decrease the specific absorption rate (SAR) 39 .…”
Section: Introductionmentioning
confidence: 99%